Enhanced performance of planar perovskite solar cells by doping the SnO2 electron transport layer with guanidinium chloride - Ye, Jiajiu; Li, Yuze; Medjahed, Asma Aicha; Pouget, Stéphanie; Aldakov, Dmitry; Liu, Yueli; Reiss, Peter (Frontiers in Materials, 2023)
Tin (IV) oxide is a highly promising electron transport layer (ETL) for lead halide perovskite solar cells due to its high conductivity, transparency, wide band gap, and the possibility of low-temperature processing. Nonetheless, charge carrier recombination processes at the SnO2/perovskite interface diminish the device performances. Here, we demonstrate that SnO2 doping with guanidine hydrochloride (G-SnO2) leads to efficient surface passivation and a larger band offset between the ETL and the perovskite layer, resulting in reduced voltage losses and faster electron transfer. Moreover, G-SnO2 facilitates the growth of highly crystalline perovskite layers. Consequently, a power conversion efficiency of up to 23.48% and a high open-circuit voltage of 1.18 V are obtained in solar cells incorporating the G-SnO2 ETL. These devices also exhibited negligible hysteresis and maintained more than 96% of their initial power conversion efficiency after 1250 h exposure to the air without encapsulation.